Methodological Bases for the Application of Innovative Technologies in the Rational Use of Natural and Economic Resources Among Elementary School Pupils - Mavlonov Shakhzod (Genius Publishing Group, 2023)
This article describes innovative methods of teaching primary school students the rational use of natural and economic resources
Keywords: Natural resources; economic resources; innovations; pedagogical technologies